Sensor Design for Building Environment Monitoring System based on Blynk - Fahmy Rinanda Saputri; Sekar Fattima Dhaneswari (Ultima Computing : Jurnal Sistem Komputer, 2022)
A green building is a building wherein planning, construction, operation until the maintenance reduces the negative impacts, such as efficient use of energy, water, and other resources, maintaining the excellent quality of the building, and considering the quality of life of occupants. Good environmental damage in the building will affect the health, comfort and, safety of the occupants' lives. Therefore, it takes green buildings concept for buildings where people do activities in a home, an office, a school, a hospital, or a community center. To implement the green building concept, the building needs a monitoring system to monitor the quality of its environment. This research aim is to design sensor systems to monitor the building environment. The parameters monitored are temperature, humidity, illuminance, and noise intensity. The sensor system needs to the integrated with microcontroller and Blynk applications. The sensor system obtains the environment parameter. The accuracy rating for the temperature sensor is 94.41%, the humidity sensor is 93.53%, the light sensor is 91.26%, and the sound sensor is 97.13%. Blynk's warning system can make it easier for users to monitor the environment of a building.